2018
DOI: 10.1371/journal.pone.0190664
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of copy number loss of the ErbB4 receptor tyrosine kinase in glioblastoma

Abstract: Current treatments for glioblastoma multiforme (GBM)—an aggressive form of brain cancer—are minimally effective and yield a median survival of 14.6 months and a two-year survival rate of 30%. Given the severity of GBM and the limitations of its treatment, there is a need for the discovery of novel drug targets for GBM and more personalized treatment approaches based on the characteristics of an individual’s tumor. Most receptor tyrosine kinases—such as EGFR—act as oncogenes, but publicly available data from th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Glioblastoma multiforme (GBM) is the most prevalent central nervous system cancer, which is the most common, severe, and difficult to treat [ 88 ]. Studies of HER family members show that HER4 is one of the most common proteins in GBM [ 89 ].…”
Section: Her4 Relationship To Different Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Glioblastoma multiforme (GBM) is the most prevalent central nervous system cancer, which is the most common, severe, and difficult to treat [ 88 ]. Studies of HER family members show that HER4 is one of the most common proteins in GBM [ 89 ].…”
Section: Her4 Relationship To Different Cancersmentioning
confidence: 99%
“…CCLE data suggests a role of HER4 as a tumor suppressor, by showing copy number loss of HER4 gene through several cell lines of GBM. However, the same variants have been shown to occur at about the same frequencies in the general population [ 88 ]. Though GBM has an average low level of HER4 expression, in 11 % of cases, high pHER4 expression was found to be present and associated with reduced survival than no pHER4 expression [ 90 ].…”
Section: Her4 Relationship To Different Cancersmentioning
confidence: 99%
“…Although the mutation rate was low, most of these genes had copy number loss. It has been demonstrated that gene copy number loss is linked to tumorigenesis [ 12 , 13 ]; for example, the loss of ErbB4 receptor tyrosine kinase is linked to the development of glioblastoma [ 14 ]. Thus, immune gene copy number loss may play a role in the development of glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism is not clear. It contains epigenetic alterations [14,15], mutation [16], copy numbers variations [17], DNA damage [18], microenvironment [19], and extracellular matrix [20]. The downregulated DEGs were significantly enriched in the extracellular matrix and the KEGG enrichment suggests that downregulated DEGs were significantly enriched in the TNF signaling pathway and the IL-17 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%